Compariison of Functtiionall Outtcomes aftter Vollar Pllattiing versus Conventtiionall PercuttaneousKiirschner Wiire Fiixattiion iin Diisttall Radiius Fracttures - Nadeem, Faisal; Amin, Muhammad Suhail; Iqbal, Muhammad Nouman; Rasheed, Muhammad Asif; Junaid, Muhammad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the functional outcomes after volar plating versus conventional percutaneous K wire fixation intreatment of distal radius fractures.Study Design: Quasi-experimental studyPlace and Duration of Study: Orthopedic Department, Combined Military Hospital, Rawalpindi Pakistan, from Aug 2023 toJan 2024.Methodology: Using consecutive non probability sampling technique, patients with displaced distal radius fractures who metthe inclusion criteria were randomized in 2 groups (65 patients in each group) and received either volar plating orpercutaneous Kirschner wire fixation. Functional outcome was recorded at 06 weeks, 03 months and then 06 months, usingquick DASH score.Results: we included 130 patients meeting inclusion criteria and equally divided them. Group-1 received open reduction andinternal fixation using volar plate as definitive treatment and Group-2 received closed reduction and percutaneous Kirschnerwire fixation. we found statistically significant functional outcome difference at 6 weeks (p=0.01), but at 03 months and 06months difference in functional outcomes in 2 groups was not found to be statistically significant (p-value 0.18 and 0.27respectively)Conclusion: The differences in functional outcomes between two modalities decrease with time and both interventions haveequivalent outcomes in long run.